Laser-Induced Breakdown Spectroscopy and Shadowgraphy of Acoustically Levitated Heptane Droplets - Parneeth Lokini; Ciprian Dumitrache; Bret C. Windom; Azer P. Yalin (Photonics)
In this study, we examined the impact of droplet size and laser energy on droplet fragmentation and the resulting species composition due to laser irradiation of an acoustically levitated heptane droplet. Using shadowgraphy and spatially resolved laser-induced breakdown spectroscopy (LIBS), we observed two different fragmentation regimes for the conditions studied. The experiments demonstrated that low laser energy densities (<~70 mJ/mm3), designated as regime 1, resulted in a single plasma breakdown event accompanied by broadband emission and C2 Swan bands, suggesting weak plasma formation. Conversely, high energy densities (>~70 mJ/mm3), designated as regime 2, resulted in multiple plasma breakdowns that resulted in the emission of Hα, O, and N, implying a full laser breakdown in the gaseous reactive mixture. Additionally, in regime 2, we calculated the electron density using Stark broadening of the Hα line and temperature using Boltzmann analysis of O lines at 715 nm and 777 nm. We found that the electron densities and temperatures within the air spark and heptane droplets are quite similar. The findings from this research could impact the design of spray ignition systems and may also aid in validating the modeling efforts of aerosols, droplet breakdown, and ignition.